Improving Students Liveliness in Islamic religius education toward PBL Learning Models Application - azzahra, rahma tiara; Soraya, Irma; hamdani, asep saepul (IAIN Ambon, 2023)
The main focus of PAI subjects is the development of student character but in reality when expected with field situations it can be seen that student participation in class is often lacking. This study aims to determine the effect of problem-based learning (PBL) on increasing student learning activities in PAI learning. Using a qualitative research approach, this research uses classroom behavior as a research design and involves high school students as participants. This study conducted interviews, observations and documentation in its data collection techniques. The results showed that there was a significant increase in student activity after implementing PBL. Students also reported better learning experiences and higher learning success. This research contributes to the development of an interactive and effective learning model to increase students' understanding and awareness of Islam.